The Effect of Aloe Vera Extract on Blood Glucose Levels in Streptozotocin-Induced Rats - Taufan Arif; Joko Pitoyo; Eddi Sudjarwo (STIKes Patria Husada Blitar, 2022)
Aloevera can protect and restore the function of damaged pancreatic beta cells. The content of aloe vera can work like insulin, and lower blood glucose even though all beta cells have degenerated. The aim of the study was to find out the effect of aloe vera extract on the regulation of blood glucose levels in rats induced by streptozotocin. The study was true experimental randomized pre-post test control group design. The sampling technique used simple random sampling consisting of 20 wistar strain rats divided into 4 groups, namely the placebo control group, treatment group with a dose of 250 mg/dl, a dose of 350 mg/dl, and a dose of 1000 mg/dl. Rats were given STZ injection on day 8 after acclimatization. The independent variable was aloe vera extract. The dependent variable was blood glucose levels. The intervention of giving aloe vera extract was given for 9 days. Data were analyzed by Paired t Test and ANOVA. The results showed that there was an effect of aloe vera extract at a dose of 350 mg/kgBW on blood glucose levels with a paired t test of 0.022. The ANOVA results showed that aloe vera extract at a dose of 350 mg/kgBW had the highest effectiveness with a p value of 0.05. The chromium, alprogen, and flavonoid in aloe vera will improve the beta function of the pancreas in producing the hormone insulin. Damage to the islets of Langerhans cells in the pancreas will be inhibited and restore the sensitivity of the insulin receptor cells.methods that are attractive to high school students and carried out consistently.